1986
DOI: 10.1111/j.1365-2044.1986.tb13281.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity after day case laparoscopy. A comparison of two techniques of tracheal anaesthesia

Abstract: SummaryA comparison was made of postoperative morbidity following two anaesthetic techniques for day case laparoscopies. One group of patienrs was allowed to breathe spontaneously after intubation under suxamethonium. The second group received atracuriwn and their lungs were mechanically ventilated. Patients in the controlled ventilation group experienced signi@cantly less severe sore throats and muscle pain in the first 24 hours postoperatively than the patients who breathed spontaneously. Both techniques pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In spite of these precautions, nearly all patients not receiving a prophylactic antiemetic experienced nausea and about 50% actually vomited. This is in keeping with the other reports of PONV in patients undergoing gynaecological surgery, particularly for laparoscopic procedures [4,7,15,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…In spite of these precautions, nearly all patients not receiving a prophylactic antiemetic experienced nausea and about 50% actually vomited. This is in keeping with the other reports of PONV in patients undergoing gynaecological surgery, particularly for laparoscopic procedures [4,7,15,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…Lonie and Harper [2] found also, in patients undergoing laparoscopy, a significantly reduced incidence of postoperative vomiting, still evident the day after operation, when nitrous oxide was omitted from the anaesthetic technique, but there was no difference in the incidence of nausea. The frequency of nausea and vomiting after day-case laparoscopy may exceed 80% [3] and might affect the patient's ability to resume normal activity. This study was designed to assess primarily the effect of nitrous oxide on nausea and vomiting and subsequent return to normal activity after day-case laparoscopy.…”
mentioning
confidence: 99%
“…17 There are several reports about there being no need for a neuromuscular block during the creation of the pneumoperitoneum. [3][4][5][6] However, there is no controlled study in the mechanically ventilated patients whether major laparoscopic surgery is possible without supplemental muscle relaxation in total i.v. anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, several studies reported anesthetic management without muscle relaxants during a short laparoscopic procedure. [3][4][5][6] Residual neuromuscular blockade and subsequent respiratory insufficiency have been reported as severe morbidity and even mortality. 7,8 No administration of supplemental muscle relaxants may reduce residual paralysis 8 and be beneficial to the safe recovery of ambulatory laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%